The Russian pediatricians contribution in creation of the International Pediatric Association (IPA) and its first congress - Alexander A. Baranov; Leyla S. Namazova-Baranova; Valery Yu. Albitskiy; Stella A. Sher; Kamilla Y. Efendieva (Union of pediatricians of Russia, 2020)
The official history of the International Pediatric Association begins on July 28, 1910, when its Charter was adopted at the meeting of the French Pediatric Association. This significant event was preceded by the years of professor I.V. Troitsky promotion of such idea as "science does not have any fatherland because the whole world belongs to it". He has encouraged pediatricians from all countries of the world for the joint work with regular discussion of the results. Professor I.V. Troitsky has developed the Charter and has defined the goal and objectives of the future International Pediatric Association, largely determining the further evolution of pediatric science.